Figurative Language in Kelly Darrow's Selected Poetry - Cicih Nuraeni; Putri Amalia Peron (LPPM Universitas Bina Sarana Informatika, 2017)
This research has the objectives proposed by the writers, they are: (1) To identify the types of figurative language used in Kelly Darrow’s selected poetry, (2) to find out the meaning of figurative language used in Kelly Darrow’s selected poetry, and (3) to know the mostly of figurative language that is used in Kelly Darrow’s selected poetry in this research. Figurative language is one of the elements of poetry that has become the poets’ way of expressing the art of his poetry and communicating his language to know the poet’s idea. Figurative language can include many words and phrases, and there are several types of figurative language. The primary sources of data are the research is conducted by using descriptive qualitative method. The data sources of this research are taken from the poetry by Kelly Darrow. Then the writersss classify the data using McKenzie’s theory of figurative language that support it. The results of this paper shows there are many types of figurative language in Kelly Darrow’s selected poetry. Kelly Darrow uses metaphor, simile, irony, personification, and hyperbole as figurative language.